Suicide by Fatal Pentobarbital Intoxication in Ontario, Canada, from 2012 to 20151. Issue 1 (24th May 2018) - Solbeck, Patricia; Snowdon, Victoria; Rajagopalan, Ashwyn; Jhirad, Reuven
Abstract: A fatal concentration of pentobarbital found in a coroner's case where the history had not indicated use of this drug prompted a review of fatalities in Ontario from 2012 to 2015. Coroner's case files, including police and toxicology reports, were reviewed in twenty deaths, in which pentobarbital was identified as the primary cause of death. In all of the deaths (11 females, 9 males), the blood concentration of pentobarbital was greater than 10 mg/L. There were three to eight deaths per year and each was classified as suicide. In 11 cases, there was clear evidence that the drug was purchased over the internet from Mexico or China and imported into Canada. In four cases, it appears that the pentobarbital was labeled as a different, innocuous chemical to facilitate crossing the border without scrutiny. The findings underscore the value of a thorough scene investigation, including details of evidence that may be considered unrelated.